Implementation of the C4.5 Algorithm for Classification of Shipping Service Data in Shipping Companies - Siti Nur Khasanah; Sandra Jamu Kuryanti; Cep Adiwihardja; Maruloh (Institute of Computer Science (IOCS), 2022)
A company engaged in the field of goods delivery services or better known as expedition services which is one of the fields that is growing rapidly with the needs of national freight forwarding services. However, from the delivery of entrustments that have been recorded, they are only stored as recording reports. With the existing problems, the current research that the author conducts aims to implement one of the algorithms in data mining, namely the C4.5 Algorithm to produce complex decisions to be simpler such as data for customers to better challenge customers with large-scale groups so as not to turn away or move to other expedition services. The results showed that the tree resulting from the C4.5 method with the C4.5 Algorithm had an accuracy percentage of 84.00%. The data processing carried out in this study used the help of the Rapid Minner application to obtain the model. The results of this study can recommend marketing the sale of freight forwarding services with the criteria of what kind of customers will get a discount.